The Limits of Hegemonic Regionalism for Explaining Region-Building: A counter-hegemonic reading of the Red Sea Council - Victoria Silva Sánchez (Cadernos de Estudos Africanos)
In the last few years, the Red Sea has witnessed unprecedented attention from scholars and policymakers. However, this does not preclude the fact that it has held enormous importance for the actors surrounding it long before. Yet, it has never qualified as a region due to a worldview deployed by hegemonic regionalism that determines what qualifies as a region. This article seeks to explain why hegemonic regionalism is ill-suited to explain regionalism in the Red Sea. We propose a theoretical framework establishing the distinct elements of hegemonic regionalism and how they have been countered by other perspectives. Then we turn towards the Red Sea Council to discuss its emergence and how it challenges the key elements of hegemonic explanations.